A Glance in the Life of Kindergarten Teachers in Hong Kong: A Mixed- Method Approach - Tang, Wing Cheung (2022)
The study has given particular attention to the kindergarten teachers' job satisfaction levels and plans to leave their current positions while they are employed in Hong Kong. Only 395 local kindergarten teachers who have experience teaching in kindergartens and who are between the ages of 18 and 60 were chosen for the study. In addition, they had to be strong communicators and be able to read and write traditional Chinese. Additionally, the research was carried out from August to October 2020. The study used a mixed-method of research. This study took into account all aspects of academic practice, including ethical research practices. For achieving the goals of the present study, numerous motivational theories, statistical analysis, and an extensive literature review were applied. According to the study, having high levels of job satisfaction has good effects and increases staff productivity; the lack of it greatly results to intentions of leaving the job. Additionally, it showed that there was a strong correlation between the communication gap between kindergarten kids and teachers and their satisfaction with their work in those settings. The level of job satisfaction is not dependent on just one factor. To address the issues raised by the study's findings, it is strongly advised to implement adequate recognition, career promotion, training programs, suitable workplace resources, and healthy work-life balance, among other things.